2023
DOI: 10.3389/fendo.2023.1227059
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate therapy of euvolemic hyponatremia, the most frequent type of hyponatremia in SARS-CoV-2 infection, is associated with increased mortality in COVID-19 patients

Mario Pazos-Guerra,
Jorge Gabriel Ruiz-Sánchez,
Xavier Pérez-Candel
et al.

Abstract: IntroductionAdmission hyponatremia, frequent in patients hospitalized for COVID-19, has been associated with increased mortality. However, although euvolemic hyponatremia secondary to the Syndrome of Inappropriate Antidiuresis (SIAD) is the single most common cause of hyponatremia in community-acquired pneumonia (CAP), a thorough and rigorous assessment of the volemia of hyponatremic COVID-19 subjects has yet to be described. We sought to identify factors contributing to mortality and hospital length-of-stay (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…CT score can predict the severity of pneumonia after SARS-CoV-2 infection ( 31 33 ), and hyponatremia can be caused by SARS-CoV-2 infection ( 34 , 35 ). Many studies have confirmed these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…CT score can predict the severity of pneumonia after SARS-CoV-2 infection ( 31 33 ), and hyponatremia can be caused by SARS-CoV-2 infection ( 34 , 35 ). Many studies have confirmed these conclusions.…”
Section: Discussionmentioning
confidence: 99%